2019
DOI: 10.1002/app.47545
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of 4,7‐dichloro‐2‐quinolinemethylacrylate‐based copolymers and their potential cytotoxic activity on human breast carcinoma cells

Abstract: In this article, an improved synthesis strategy of the potent anticancer compound 4,7-dichloro-2-quinolinemethanol (QM) and its acrylate ester 4,7-dichloro-2-quinolinemethylacrylate (AQM) are described. AQM is copolymerized using free-radical polymerization with N-vinyl-2-pyrrolidone (VP) and the copolymers obtained from different molar ratios of monomers are subjected to nanoprecipitation to produce suspensions of nanoparticles (NPs) in phosphate buffered saline (PBS). The smallest and stable NPs are prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The thermal stability of the copolymers (~5 mg) was analyzed by thermogravimetric analysis using a TGA Q500 (TA Instruments, New Castle, DE, USA) under a nitrogen atmosphere (50 mL min −1 ) at 10 • C min −1 heating rate from 25 to 600 • C. Both the onset and weight loss values were calculated using TA Instruments Universal Analysis Software (v. 4.5A). [14,32] To obtain unloaded NPs, copolymer solutions were prepared in THF:DMF (7:3) with a 5 mg mL −1 concentration. A total of 2.5 mL of each solution was added dropwise to 10 mL of PBS (phosphate buffered solution, pH 7.4), i.e., in 1:4 (v/v) proportion, under constant magnetic stirring, and then was dialyzed against PBS for 24 h (with a membrane of 3.5 kDa molecular weight cutoff) to remove the organic solvent.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
“…The thermal stability of the copolymers (~5 mg) was analyzed by thermogravimetric analysis using a TGA Q500 (TA Instruments, New Castle, DE, USA) under a nitrogen atmosphere (50 mL min −1 ) at 10 • C min −1 heating rate from 25 to 600 • C. Both the onset and weight loss values were calculated using TA Instruments Universal Analysis Software (v. 4.5A). [14,32] To obtain unloaded NPs, copolymer solutions were prepared in THF:DMF (7:3) with a 5 mg mL −1 concentration. A total of 2.5 mL of each solution was added dropwise to 10 mL of PBS (phosphate buffered solution, pH 7.4), i.e., in 1:4 (v/v) proportion, under constant magnetic stirring, and then was dialyzed against PBS for 24 h (with a membrane of 3.5 kDa molecular weight cutoff) to remove the organic solvent.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
“…24 This double biological activity is probably due to the similarity of certain biochemical processes of human and bacterial cells (e.g., cell division or cellular respiration) in which structurally similar biomolecules participate, which would be the therapeutic target for these quinolinic drugs. 8 It is noteworthy that Valle et al recently reported the synthesis of the new molecule AQM, which showed potent cytotoxic activity against breast carcinoma cells MDA-MB-453 (IC50: 19 μM); 25 however, its potential antibacterial activity has not been evaluated. In the present work, we investigated the antibacterial activity of AQM on six bacterial species, two pathogenic bacteria for humans (Klebsiella pneuminiae and Staphylococcus aureus), three phytopathogenic bacteria (Pcc, Ralstonia solanacearum and Pseudomonas syringae) and Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%